International financial management - Madura, Jeff (South-Western College Pub., 2008)
INTERNATIONAL FINANCIAL MANAGEMENT strives to build on the foundation of corporate finance. Recognizing that multinational corporations continue to globally expand, this text first provides a background on the international environment and then focuses on the managerial aspects from a corporate perspective. This book gives you the tools to understand the international financial environment so that you can manage within it